Pelatihan Simulasi Gerbang Dasar Meggunakan Electronic Workbench (EWB - Hoiriyah Hoiriyah; Fakhriani Ekawati; Lilis Anggraini (Jurnal Informasi Pengabdian Masyarakat, 2023)
Informatics is a field of science regarding the study of design and development of computing systems, in which there is a logic gate that can receive one or more input data, but only has one output, the output of which is high (1) or low (0). depending on the output results of the input process, the operation must follow the rules in logical algebra or Boolean algebra in a binary system in which there are basic gates, namely OR, AND and NOT. Basically, students have difficulty understanding the gates directly in Boolean algebra and applying them to digital circuits, which makes students confused and difficult to implement them in real terms in the circuit. In general, the training was familiar with basic logic gates well, in terms of ability to use the application, the increase was 89% and was categorized as capable. So, it can be concluded that all participants who took part were able to implement the EWB application and were declared to have improved in skill.